X-linked mental retardation associated with macro-orchidism. Issue 4 (December 1975) - Turner, G; Eastman, C; Casey, J; McLeay, A; Procopis, P; Turner, B
Abstract : Two families are described with an X-linked form of mental retardation in whom the affected males were found to have bilateral enlargement of the testes. No conclusive evidence of any endocrinological disturbance was found.